Forestry activity articles in selected Nigeria newspapers (2013)
Reportage of forestry activities in Nigeria newspapers had been given little attention over the years, despite the importance of forestry sector to national development. This study examined press coverage of forestry activities with the view to establishing the roles played by the press in the development and preservation of forest and forest products in Nigeria. Data were obtained from four (4) the national newspapers with wide coverage and high readership ratings. Through content analysis multistage sampling technique produced 63 articles from the newspapers. On yearly basis, year 2010 had the highest frequency of forestry article reportage activity articles. In all the newspapers, the newshole allotted to forestry articles are usually small and many of the articles were placed on non-prominent pages. Furthermore, forestry activity articles were reported more during the wet season having a total of 73.02%, while dry season had 26.98% of the reported forestry activity articles. Also, 46.03% of reported forestry activity articles had no accompanying pictures. There were no observable differences in the level of reportage of forestry activities in the selected Nigerian newspapers. Thus, it is recommended that the Nigerian Press Council should encourage their members to give more attention to the reportage of forestry activities, so as to increase the level of awareness about the importance of forestry and its contribution to National development.